2016
DOI: 10.1097/aln.0000000000001320
|View full text |Cite
|
Sign up to set email alerts
|

STR-324, a Stable Analog of Opiorphin, Causes Analgesia in Postoperative Pain by Activating Endogenous Opioid Receptor–dependent Pathways

Abstract: Background Opiorphin is a naturally occurring potent analgesic human peptide. It protects enkephalins from degradation and inhibits pain perception in various acute pain models via activation of endogenous opioid pathways. However, the efficacy of opiorphin continuous infusion and its chemically stable form, STR-324, in postoperative pain is unknown. Methods Using the Brennan model of plantar incision–induced hypersensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Rougeot et al suggested that opiorphin interacts indirectly with opioid receptors (Toth et al, 2012;Benyhe et al, 2014;Sitbon et al, 2016). This was proposed based on two findings (Toth et al, 2012) The finding of the present study that sialorphin did not affect the binding affinity of [ 3 H] DAMGO is in agreement with this earlier observation.…”
Section: Downloaded Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…Rougeot et al suggested that opiorphin interacts indirectly with opioid receptors (Toth et al, 2012;Benyhe et al, 2014;Sitbon et al, 2016). This was proposed based on two findings (Toth et al, 2012) The finding of the present study that sialorphin did not affect the binding affinity of [ 3 H] DAMGO is in agreement with this earlier observation.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…Administration of either was reported to induce an antinociceptive effect through activation of opioid receptors (Rougeot et al, 2003;Wisner et al, 2006). Rougeot and colleagues suggested that opiorphin protects enkephalins from degradation by two peptidases (NEP and APN), thus improving the affinity of enkephalins without directly interacting with opioid receptors itself (Toth et al, 2012;Benyhe et al, 2014;Sitbon et al, 2016). Increasingly, compounds are being discovered that directly modulate receptors via distinct allosteric rather than orthosteric sites.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The improved safety of KK-103 might be explained by its high structural similarity to the endogenously produced Leu-ENK. Indeed, various compounds harnessing the endogenous ENK system have been demonstrated to exhibit improved safety without inducing typical side effects caused by MOR agonists, including respiratory depression, tolerance, physical dependence, and constipation [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous infusion of tritiated STR-324 in monkeys, a selective sequestration of the radioactive peptide was observed in the spinal and cerebral tissues indicating its ability to cross BBB. 4,12 The gene, currently named PROL1 gene, coding the PRL1 is a precursor protein of opiorphin mature peptide product, identified by Dickinson et al, is expressed in human lacrimal and salivary glands. The concentration of opiorphin in human saliva was quantified as 2.8 to 25.9ng/ml.…”
Section: Opiorphin: the Promising Alternativementioning
confidence: 99%
“…17 In spite of the captivating leads of opiorphin peptide, its pharmaceutical development is hindered by its low stability, typical of N-terminal glutamine peptides. 12 The metabolic half-life of opiorphin is 5min owing to it rapid degradation by circulating peptidases. 6…”
Section: Opiorphin: the Promising Alternativementioning
confidence: 99%